Analisis Burnout guru dalam pembentukan karakter siswa di SDN Setia Darma 04 - putri, Aliera azzahra; Yohamintin Yohamintin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the burnout conditions experienced by teachers and their impact on the formation of student character at SDN Setia Darma 04. Using a qualitative approach with case study methods, data was collected through observation, interviews, and documentation. Research results show that burnout in teachers negatively affects students' attitudes and character formation, such as decreased discipline, responsibility, and confidence. Teachers who experience emotional exhaustion, cynicism, and decreased self-performance tend to be less than optimal in providing exemplary and character guidance. This shows the importance of emotional support and coping strategies for teachers in order to effectively perform the role of character coaching. This study is expected to be a reference in improving character development policies in primary schools.